Improving Students' Writing Skills Through Picture Series at 6th Semester of English Department Education of HKBP Nommensen University - Agnes Tiomadina Tambunan; Yohana Friscila Naibaho; Jona Hutasoit; Dr. Rina Octavia Simarmata (Merwin Publisher, 2024)
Abstract This study emphasizes how difficult it is for students to formulate and arrange their thoughts in descriptive writing, as well as how little teachers focus on their understanding of the content they are teaching. The goal of the study is to examine how pupils in the tenth grade have improved their writing abilities. By using pictures in conjunction with visual aids. Using qualitative information was obtained by means of classroom observations. The subjects of this study are the sixth semester English Department Education students at HKBP Nommensen University, who are given visual assistance in the form of graphics to help them write better. The results show that when pictures are used creatively and positively, students write with greater engagement, drive, and originality, which produces compositions that are noticeably better. The major areas of emphasis are the significance of visual aids in helping students' writing learning processes and the efficacy of creative teaching tactics. The significance of a mixed-methods approach for a thorough comprehension of pedagogical interventions in education is emphasized in this essay. The study highlights the necessity of creative pedagogical techniques in educational situations while offering profound insights into the function of pictures as stimuli in improving students' writing abilities. The ramifications of these research findings further highlight how important it is to use visual aids in the classroom, since they greatly improve the caliber of instruction. Keywords: Classroom,Writing Skill, Picture, Student